2018
DOI: 10.1016/j.renene.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental validation of a transient 2D numeric model for radiant walls

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons 1 Development and experimental validation of a transient 2D numeric model for radiant walls

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Previous research related to the present article showed the peak load shifting capability of radiant walls [25], even under internal loads [26]. Moreover, the experimental research was used to validate a numerical model of the radiant wall [27]. This was later implemented in a control study that showed that the potential of the PV array was only exploited if the heat pump was operated under a specific solar control [28].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous research related to the present article showed the peak load shifting capability of radiant walls [25], even under internal loads [26]. Moreover, the experimental research was used to validate a numerical model of the radiant wall [27]. This was later implemented in a control study that showed that the potential of the PV array was only exploited if the heat pump was operated under a specific solar control [28].…”
mentioning
confidence: 89%
“…Additionally, the model was used to evaluate the most important design parameters of the radiant wall, more details on the validation and the parametric studies were presented in Romani et al [25]. Afterwards, the radiant wall model was integrated to the whole room model, which was developed according to the Seem methodology [27] considering six surfaces. Four walls (East, South, West, and North), ceiling slab, and floor slab are modelled.…”
Section: Simulation Modelmentioning
confidence: 99%
“…Although empirical validation procedures, based on real metering and auditing data, are considered as very reliable procedures [47], they are often used for the validation of tools and mathematical models developed for simulating specific phenomena. In this regard, the literature shows several examples of such a procedure applied to the validation of models relative to thermally activated building systems [48][49][50], daylighting or HVAC interactions with respect to window or solar gain [51,52], double skin facades or ventilated cavity [53][54][55][56], activities of occupants and their interaction with the building loads [57], etc. It is worth noting that though experimental validations of single mathematical models for the simulation of the energy performance of a specific new building's technology, component or material, can be often easily carried out, the experimental validation of whole BEPS tools is mostly unfeasible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous research, a 2D transient finite volume model of a radiant wall was developed and experimentally validated [26]. However, this model only described the behaviour of the radiant wall, which required, among other inputs, the indoor temperature.…”
Section: Model Descriptionmentioning
confidence: 99%
“…These approach was based in previous experimental research on radiant wall cubicle, which showed good energy savings potential and peak load shifting capability [24,25]. From this experimental research, a numerical model of the radiant wall was validated [26] and then implemented in the current research.…”
Section: Introductionmentioning
confidence: 99%